A Scoping Review of the Relationship Between Psychological (In)flexibility and Living with and Managing Type 1 and Type 2 Diabetes - Max Z. Roberts; Francesca A. Scheiber; Ashley A. Moskovich; Rhonda M. Merwin (Behavioral Sciences)
Diabetes Mellitus (DM) is highly prevalent and carries a significant self-management burden and elevated risk of biopsychosocial sequelae. Psychological flexibility (PF) has been shown to benefit living with and managing chronic health conditions. The present scoping review aimed to synthesize the available evidence on the relationship between PF and factors central to living with and managing DM. A systematic literature search was conducted. Studies were included if they measured psychological (in)flexibility (PI/PF) and/or one of its component processes and sampled individuals with type 1 or type 2 DM. A total of 48 articles were included. Eighteen (37.5%) sampled individuals with T2D, 16 (33.3%) sampled individuals with T1D, and 14 (29.2%) had mixed diagnostic samples. Twenty-nine (60.4%) reported observational studies, and 19 (39.6%) reported 18 intervention studies. Studies were conducted across 17 countries and broadly found that PI/PF were associated with many clinically meaningful DM variables (e.g., HbA1c, diabetes distress, quality of life, and self-management). Intervention studies including individual, group, and digital Acceptance and Commitment Therapy (ACT) interventions showed trends for beneficial change in PI/PF and diabetes outcomes, but some findings were mixed, and many studies were underpowered. Only two studies tested change in PI/PF as a mediator of diabetes-related outcomes, and most studies used the Acceptance and Action Questionnaire, which has been increasingly criticized for poor discriminant validity. Overall, findings show PI/PF are associated with most aspects of living with and managing diabetes and are generally amenable to change through ACT interventions. However, more methodologically rigorous studies are needed to determine whether PI/PF are active change processes in improving diabetes management and outcomes. Six key calls to action are presented to expand and strengthen this important area of research.